Literature Study: The Effectiveness of Aromatherapy on Reducing Anxiety in Chronic Kidney Failure Patients Undergoing Hemodialysis - Eka Agustin; Dian Hudiyawati (Journal of Nursing Science Update (JNSU), 2021)
Chronic Kidney Disease (CKD) is a progressive and irreversible decline in kidney function that results in the decreased ability of the body to retain fluids and electrolytes. Treatment methods in end-stage kidney disease are long-term treatment with hemodialysis and kidney transplantation. Hemodialysis therapy in the long term can cause anxiety. Aromatherapy can assist patients in coping with anxiety. The goal of this study was to determine the efficacy of aromatherapy in reducing anxiety in patients with hemodialysis. Articles were obtained through online databases such as PubMed, Google Scholar, and Science Direct. There are seven articles obtained after going through data screening and will be identified for critical review. The findings show that inhalation aromatherapy was effective in reducing anxiety levels among hemodialysis patients. Inhaled aromatherapy affects the central nervous system and has a balancing effect on the cerebral cortex and nerves in the brain. Inhaled aroma compounds will interact quickly through the central nervous system and olfactory nerves and then stimulate the nerves in the brain under the balance of the cerebral cortex to produce the release of the hormone melatonin, serotonin, which can cause a feeling of relaxation or sedative.Â  Future research should include a variety of aromatherapy variants that can be used based on patient preferences, as well as an assessment of possible side effects.